Persistent Structure and Frustrated Magnetism in High Entropy Rare‐Earth Zirconates. Issue 5 (25th November 2021) - Jothi, Palani R.; Liyanage, WLNC; Jiang, Bo; Paladugu, Sreya; Olds, Daniel; Gilbert, Dustin A.; Page, Katharine
Abstract: The configurational complexity and distinct local atomic environments of high entropy oxides remain largely unexplored, leaving structure‐property relationships and the hypothesis that the family offers rich tunability for applications ambiguous. This work investigates the influence of cation size and materials synthesis in determining the resulting structure and magnetic properties of a family of high entropy rare‐earth zirconates (HEREZs, nominal composition RE2 Zr2 O7 with RE = rare‐earth element combinations including Eu, Gd, Tb, Dy, Ho, La, or Sc). The structural characterization of the series is examined through synchrotron X‐ray diffraction and pair distribution function analysis, and electron microscopy, demonstrating average defect‐fluorite structures with considerable local disorder, in all samples. The surface morphology and particle sizes are found to vary significantly with preparation method, with irregular micron‐sized particles formed by high temperature sintering routes, spherical nanoparticles resulting from chemical co‐precipitation methods, and porous nanoparticle agglomerates resulting from polymer steric entrapment synthesis. In agreement with the disordered cation distribution found across all samples, magnetic measurements indicate that all synthesized HEREZs show frustrated magnetic behavior, as seen in a number of single‐component RE2 Zr2 O7 pyrochlore oxides. These findings advance the understanding of the local structure of high entropy oxides and demonstrate strategies for designing nanostructured morphologies in the class. Abstract : The structure and magnetic properties of a family of nanostructured high entropy rare‐earth zirconates (HEREZs) with nominal compositions RE2 Zr2 O7 (RE = rare‐earth elements) are presented. Local order, magnetic behavior, and homogenous cation distributions are found persistent across multiple synthesis routes, compositions, and sample morphologies, contributing to a deeper understanding of tunability in the high entropy oxide class.